PENDIDIKAN MANUSIA-MANUSIA DEMOKRATIS FILSAFAT PENDIDIKAN NOAM CHOMSKY RELEVANSI SERTA KETERBATASANNYA PADA KONTEKS INDONESIA - Reza A.A Wattimena (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2012)
Education is the backbone of a civilized society. In the democratic society, education plays an important role to create, spread, and maintain the democratic ideals. That is the main idea in Noam Chomsky’s philosophy of education. There is a deep connection between democratic principles on the one hand, and democratic education paradigm on the other hand. However, these ideal is threatened by authoritarian way of thinking that exist in totalitarian ideology and capitalistic way of thinking. These two ideologies repress human freedom, and destroy democratic culture which is the bed rock of democratic society. Chomsky offers us a knowledge concerning the way to redesign education in facing the challenges of democratic society.